(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
During preschool childhood, profound changes occur in a child’s thinking. A preschooler begins to distinguish the properties of surrounding objects, understand the simplest connections between them, and use these connections in his manipulations. This creates the necessary conditions for further mental development, is associated with the development of elementary forms of play and drawing, and speech.